Comparative Analysis of Gene-Expression Patterns in Human and African Great Ape Cultured Fibroblasts - Karaman, Mazen W. (Cold Spring Harbor Laboratory Press, 2003)
Although much is known about genetic variation in human and African great ape (chimpanzee, bonobo, and gorilla) genomes, substantially less is known about variation in gene-expression profiles within and among these species. This information is necessary for defining transcriptional regulatory networks that contribute to complex phenotypes unique to humans or the African great apes. We took a systematic approach to this problem by investigating gene-expression profiles in well-defined cell populations from humans, bonobos, and gorillas. By comparing these profiles from 18 human and 21 African great ape primary fibroblast cell lines, we found that gene-expression patterns could predict the species, but not the age, of the fibroblast donor. Several differentially expressed genes among human and African great ape fibroblasts involved the extracellular matrix, metabolic pathways, signal transduction, stress responses, as well as inherited overgrowth and neurological disorders. These gene-expression patterns could represent molecular adaptations that influenced the development of species-specific traits in humans and the African great apes.